Taking on the Pledge of Allegiance : the news media and Michael Newdow's Constitutional challenge - Bishop, Ronald, 1961- (State University of New York Press, 2007)
"Taking on the Pledge of Allegiance explores the landmark lawsuit filed by avowed atheist Michael Newdow against the Elk Grove Unified School District in California, in which he claimed the words "under God" in the Pledge of Allegiance amounted to an unconstitutional endorsement of religion." "This book contains interviews with many of the parties involved, including Newdow and journalists who covered the case. Ronald Bishop examines how the news media marginalized Newdow after the Ninth Circuits ruling - acting as a "guard dog" for the government and for the ideas supposedly at the ideological heart of America - by framing the decision as an aberration, a radical act by a hopelessly liberal federal circuit court. Bishop concludes that journalists relegated Newdow to a rhetorical "protest zone"--He was heard, but from a safe distance."--Jacket